2016
DOI: 10.1186/s12610-016-0039-2
|View full text |Cite
|
Sign up to set email alerts
|

Gonadal response after a single-dose stimulation test with recombinant human chorionic gonadotropin (rhCG) in patients with isolated prepubertal cryptorchidism

Abstract: BackgroundThe evaluation of prepubertal gonadal Leydig cells secretion requires gonadotropin stimulation. Urinary hCG (human chorionic gonadotropin) is currently unavailable in many countries, however, recombinant hCG (rhCG) can be used. Our aim was to evaluate rhCG-stimulated testicular hormones in a group of patients with cryptorchidism.MethodsWe evaluated 31 prepubertal boys (age range, 0.75–9.0 years) presenting with unilateral (n = 24) or bilateral (n = 7) cryptorchidism. Patients with other genital abnor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
15
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 17 publications
3
15
0
Order By: Relevance
“…These data agree with other studies, while others reported lower peak values mainly using single hCG for stimulation [Saenger et al, 1978;Forest, 1979;Balducci et al, 1986;Savage, 1992;De Martino et al, 2003;Oliveira et al, 2016] ( Table 2 ). A stimulated increase <1.1-1.5 ng/mL is considered as a subnormal response [Forest, 1979;Balducci et al, 1986;Savage, 1992;Mendonca et al, 2010;Ishii et al, 2015].…”
Section: Hcg Test: Normative Criteriasupporting
confidence: 82%
See 2 more Smart Citations
“…These data agree with other studies, while others reported lower peak values mainly using single hCG for stimulation [Saenger et al, 1978;Forest, 1979;Balducci et al, 1986;Savage, 1992;De Martino et al, 2003;Oliveira et al, 2016] ( Table 2 ). A stimulated increase <1.1-1.5 ng/mL is considered as a subnormal response [Forest, 1979;Balducci et al, 1986;Savage, 1992;Mendonca et al, 2010;Ishii et al, 2015].…”
Section: Hcg Test: Normative Criteriasupporting
confidence: 82%
“…It is more expensive, but the rhCG shows remarkable batch-to-batch consistency, high specific activity, lack of potential biological risk, and high purity, being free from contaminant proteins [Zegers-Hochschild et al, 1995]. Finally, rhCG permits the test in countries in which uhCG is unavailable [Oliveira et al, 2016].…”
Section: Hcg Test: New Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Males that produce insufficient testosterone suffer from reduced fertility, but in some mammalian species, this can be improved with hormone therapy. 7,8 For instance, hCG can be used to increase follicle-stimulating hormone (FSH) and luteinizing hormone (LH) levels, which then stimulates the Leydig cells to secrete testosterone. 8 After injecting hCG into bulls, plasma LH has been reported to increase after a few minutes, stimulating testosterone production.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 For instance, hCG can be used to increase follicle-stimulating hormone (FSH) and luteinizing hormone (LH) levels, which then stimulates the Leydig cells to secrete testosterone. 8 After injecting hCG into bulls, plasma LH has been reported to increase after a few minutes, stimulating testosterone production. 9 The present results suggests that in ibexes, the administration of hCG can induce a temporary increase in plasma testosterone, which can help the testes relocate to the scrotum.…”
Section: Discussionmentioning
confidence: 99%